Development of a university innovation ecosystem assessment model for Association of Southeast Asian Nations universities - Chaipongpati, Jirawan; Thawesaengskulthai, Natcha; Koiwanit, Jarotwan (My University, 2022)
Universities are centres of innovation and technology transfer, and they play a particularly strong role in the countries of the Association of Southeast Asian Nations (ASEAN) with developing technology programs. However, there are only a few assessment tools for evaluating a university’s innovation ecosystem, and these tools are frequently lacking either in terms of process orientation or in other gaps. The objective of this research was to develop a model of an innovation ecosystem for an ASEAN university and to identify the relative importance of each factor. A multi-method approach was used. In the Stage 1 research, a Delphi study of ASEAN-based university innovation experts (n = 40) was conducted. This research resulted in a preliminary assessment tool. This tool was then evaluated through a broader survey of university innovation experts in ASEAN (n = 418). The data were analysed using confirmatory factor analysis. The results identified a total of 21 innovation areas in four role-based domains: Leaders and Governors, Educators, Innovators and Connectors. The resulting assessment instrument is suitable for use in university innovation ecosystem development and policy making.
Keywords: entrepreneurial university; higher education; quality assurance; university assessment; University innovation ecosystem